Pengaruh Fleksibilitas Jam Kerja Dan Work Life Balance Terhadap Kinerja Karyawan PT Pernas - Ega Azhari; Arga Sutrisna; Arif, Arif (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2025)
This study purposse to identify and analyze the description of Work Schedule Flexibility, Work-Life Balance, and Employee Performance at PT PERNAS in Tasikmalaya Regency. It also aims to examine the simultaneous effect of Work Schedule Flexibility and Work-Life Balance on Employee Performance at PT PERNAS in Tasikmalaya Regency, as well as the partial effect of Work Schedule Flexibility and Work-Life Balance individually on Employee Performance at the same company. The method used in this study is descriptive quantitative, with a sample of 140 employees of PT PERNAS in Tasikmalaya Regency serving as respondents. The data used includes both primary and secondary data. The analytical tool applied in this study is multiple linear regression using the SPSS version 25 application for data processing. The results of the study indicate that Work Schedule Flexibility among employees at PT PERNAS is classified as good, Work-Life Balance is also classified as good, and Employee Performance is classified as high. Based on the findings, it can be concluded that Work Schedule Flexibility and Work-Life Balance simultaneously have a significant effect on employee performance at PT PERNAS in Tasikmalaya Regency. Furthermore, the study also concludes that both Work Schedule Flexibility and Work-Life Balance have significant partial effects on employee performance.